Ecological risks of demersal fishing on deepwater chondrichthyan populations in the Southern Indian and South Pacific Oceans. (24th March 2020) - Georgeson, L; Rigby, C L; Emery, T J; Fuller, M; Hartog, J; Williams, A J; Hobday, A J; Duffy, C A J; Simpfendorfer, C A; Okuda, T; Stobutzki, I C; Nicol, S J
Abstract: Risks to deepwater chondrichthyans (sharks, rays, and chimaeras) from fishing are poorly understood, particularly in areas beyond national jurisdiction. We adapted productivity–susceptibility analysis (PSA) and sustainability assessment for fishing effects (SAFE) to assess the vulnerability of 173 deepwater chondrichthyans to various demersal fishing gears in the Southern Indian and South Pacific Oceans. Several species were categorized as being at high or extreme vulnerability, including some deepwater shark species in the Southern Indian Ocean that are reported to be commercially targeted. There was good concurrence between PSA and SAFE results for species categorized as being at high or extreme vulnerability by the SAFE, but as expected there was an overall greater number assessed to be as higher vulnerability using PSA due to its precautionary nature. Our results indicate probable misclassifications in the PSA relative vulnerability rankings, highlighting the value of applying more quantitative tools, such as SAFE, when adequate data are available. Our findings indicate that better catch, effort, and biological information are needed to inform the assessment and management of deepwater chondrichthyans. If targeted fishing of deepwater shark species continues in the Southern Indian Ocean, improved assessments and estimates of sustainable yields are urgently required to mitigate the risk of overexploitation.